2005
DOI: 10.1203/01.pdr.0000148066.34743.10
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Transients in Infant Human Atrial Myocytes

Abstract: Isolated infant human atrial cells have a slower early repolarization than adult human atrial cells. In addition, from room temperature voltage-clamp studies, infant cells have lower basal L-type calcium currents than adult cells. We hypothesized that the slower repolarization increases the calcium transient of infant human atrial cells. Atrial myocytes were enzymatically dissociated from biopsies of human right atrial appendages of infant (3-8 mo) patients who were undergoing open-heart surgery. Intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(31 reference statements)
3
6
0
Order By: Relevance
“…Optical recordings of intracellular calcium transients by line scans reflected appropriate cyclic calcium handling (Figure 1E). The average spontaneous beating frequency for these cells was 0.49 Hz, which was in the range reported in the literature for functional hESC-CMs (Lundy et al., 2013), and the amplitude was also consistent with what has been measured in human cardiac cells (Wagner et al., 2005). Other measured parameters, including times to 50% peak and to 50% decay, were also representative of a cardiac-type phenotype.…”
Section: Resultssupporting
confidence: 89%
“…Optical recordings of intracellular calcium transients by line scans reflected appropriate cyclic calcium handling (Figure 1E). The average spontaneous beating frequency for these cells was 0.49 Hz, which was in the range reported in the literature for functional hESC-CMs (Lundy et al., 2013), and the amplitude was also consistent with what has been measured in human cardiac cells (Wagner et al., 2005). Other measured parameters, including times to 50% peak and to 50% decay, were also representative of a cardiac-type phenotype.…”
Section: Resultssupporting
confidence: 89%
“…It indicates that sodium channel is closed more slowly in pediatric atrial myocytes than adults, and the number of sodium ion flowing into cytoplasm through single sodium channel tend to be larger in pediatric atrial cells than adults at the late stage of channel inactivation, which is likely to cause the delay of membrane early repolarization and the prolongation of action potential duration. Consistently, it was previously reported that action potential duration was significant longer in infant atrial cells than adults during the early period of membrane potential repolarization 24, 26. Similarly, the difference of voltage-dependent activation and inactivation of sodium channels were studied and adult atrial cells exhibited the similar voltage-dependent activation and more slow voltage-dependent inactivation compared with pediatric atrial cells.…”
Section: Discussionsupporting
confidence: 81%
“…During early postnatal development, SR contribution to Ca 2+ cycling, although important, is smaller than in adult myocardium (1,41), probably due to structural SR underdevelopment and paucity of sarcolemma-SR specialized junctions, as well as to diminished sensitivity of the CICR mechanism (18 (43). Similar results were observed in myocytes from senescent animals (44), which present, as neonatal cells, reduced I to density and prolonged AP (30).…”
Section: How I To Can Affect Ca 2+ Homeostasismentioning
confidence: 83%